Analisis Sistem Pengendalian Intern Penerimaan dan Pengeluaran Kas pada PT. Raja Marga Cabang Nagan Raya - Yulita, Yana; Zhafira, Nabila Hilmy (Regress: Journal of Economics & Management, 2022)
controls that help assess the possible outcomes of various activities and actions that can be followed up. The purpose of this study was to determine the effectiveness of the implementation of the internal control system on cash receipts and disbursements at PT. Raja Marga. This study used descriptive qualitative method. The data used are primary data and secondary data. Data collection techniques using interview techniques, observation and documentation. The results showed that the internal control system applied to PT. Raja Marga has been running well in accordance with the elements of COSO's internal control which can be seen from the organizational structure of PT. Raja Marga in the division of authority and functional responsibilities has been carried out according to their respective duties. The conclusion that can be drawn is that PT. Raja Marga has carried out internal control properly in accordance with COSO elements. Companies must maintain this so that internal control of cash receipts and disbursements continues to run well.